Effects of Trait Anxiety on Error Processing and Post-error Adjustments: An Event-Related Potential Study With Stop-Signal Task - Hsieh, Meng-Tien; Lu, Hsinjie; Lin, Chia-I; Sun, Tzu-Han; Chen, Yi-Ru; Cheng, Chia-Hsiung (Frontiers in Human Neuroscience, 2021)
The present study aimed to use event-related potentials with the stop-signal task to investigate the effects of trait anxiety on inhibitory control, error monitoring, and post-error adjustments. Stop-signal reaction time (SSRT) was used to evaluate the behavioral competence of inhibitory control. Electrophysiological signals of error-related negativity (ERN) and error positivity (Pe) were used to study error perception and error awareness, respectively. Post-error slowing (PES) was applied to examine the behavioral adjustments after making errors. The results showed that SSRT and PES did not differ significantly between individuals with high trait anxiety (HTA) and those with low trait anxiety (LTA). However, individuals with HTA demonstrated reduced ERN amplitudes and prolonged Pe latencies than those with LTA. Prolonged Pe latencies were also significantly associated with poorer post-error adjustments. In conclusion, HTA led to reduced cortical responses to error monitoring. Furthermore, inefficient conscious awareness of errors might lead to maladaptive post-error adjustments.